Draft Annual Plan 1979-80 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1979)
For the year 1973-79, the Planning Commission approved a Plan of Rs 449,00 crores and this was provided in the Vote-on-Account budget of the State. Subsequently, an exercise to re-orient the Plan priorities with a view to giving greater emphasis to measures intended to tackle the problem of unemployment, provision of Minimum Needs to the people in rural and urban areas and welfare of weaker sections of the population, was undertaken by the Government and as a result of this, the Plan outlay for 1978-79, has been increased to Rs 477.57 crores and this outlay has been provided in the final budget of the State Government.
Finance and Planning (Planning Wing) Department Hyderabad